Yesus Sejarah dan Kristus Iman - L M, YUSUF (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2020)
One of the most hotly debated topics in the 18th century and its peak in the 19th century was The Jesus of history and The Christ of faith. This topic became very popular for the theologians and professors of the New Testament to analyze. The work done in this analysis always leads to the conclusion that the Jesus who is believed by Christians today is an unhistorical Jesus. Sources of the Gospels - The gospel held today is often considered to be inaccurate and distorted by the delusions of the gospel writers. But all the accusations of the liberal theologians are not based on historical facts and contradict the authenticity of the canonical gospels. Salah satu topik yang sangat panas diperdebatkan pada abad 18 dan puncaknya pada abad 19 adalah The Jesus of history dan The Christ of faith. Topic ini menjadi sangat popular untuk dianalisis para teolog dan para professor Perjanjian Baru.Upaya yang dilakukan dalam analisis ini selalu berujung kepada sebuah kesimpulan bahwa Yesus yang diimani oleh orang Kristen masa kini adalah Yesus yang tidak historis.Sumber Injil-Injil dipegang saat ini sering dianggap tidak akurat lagi dan sudah terdistorsi oleh khayalan para penulis Injil.Namun semua tuduhan para teolog liberal itu tidak berdasarkan fakta sejarah dan bertentangan dengan keotentikan kitab Injil Kanonik.